Water uptake and pre-germination treatments in macaw palm (Acrocomia aculeata - Arecaceae) seeds - Rodrigues Junior,Ailton Gonçalves (2013)
The aims of this study were to evaluate the influence of embryo adjacent tissues in water uptake and treatments to release dormancy in macaw palm seeds. To assess water absorption with or without the opercular tegument (OT), seeds were immersed in water for 0, 12, 24, 48, 72, 96, 120, 168, 240, 360, 480 and 720 hours and the water content of isolated embryos and seeds was determined. In seeds with or without OT, gibberellic acid (GA3) solutions at concentrations of 0, 50, 100, 500, 1000 and 2000 mg.L-1 were applied on the OT region using a culture medium. In another experiment, the OT was removed or left intact and the seeds immersed in hydrogen cyanamide solutions (0, 0.5, 1, 1.5, 2 and 2.5%). The percentage germination, germination speed index (GSI) and percentage dead seeds were determined. The OT does not prevent embryo water uptake but reduces water absorption speed. The use of GA3 in a culture medium applied to the OT region did not effectively release dormancy. The use of cyanamide at these concentrations increased seed mortality, resulting in a low germination. OT removal increased the GSI.